Maritime piracy at Strait of Malacca, Malaysia - Alias, Eunica Syrah; Ismail, Mohd Azril (2012)
The Straits of Malacca is one of the busiest and most important strategic waterways in the world.The location of Straits of Malacca makes the waterway facing the piracy problem.Piracy can be described as the hijacking of ships or crews or both.The study will discuss further about the maritime piracy at Straits of Malacca, factors of maritime piracy, and the accountability of government and private sector to face this phenomenon.A good cooperative needed in this problem to avoid any negative impact to the nation.